The Rhetorical Ties That Bind (or Divide): President Barack Obama's Attitude of Tolerance in an Age of Ultra-partisanship - (:unkn) unknown (My University, 2016)
In this dissertation, I explore how President Barack Obama’s rhetoric seeks to shift conversations away from traditional notions of the political and into more localized discussion and forms of civic engagement. Using three case studies from his second presidential term, I stress that Obama’s rhetoric illustrates how a leader can use speech as the incipient act for fomenting a new attitude toward civic engagement. For Obama, this involved shifting the locus for political change away from Washington and lawmakers and onto the American electorate themselves. To empower individuals, Obama’s rhetoric stressed that ultra-partisanship was a contagion facing America in the 21st century, but not a terminal illness. To bypass conflict affiliated with ultra-partisanship, Obama advocated that Americans adopt an attitude of tolerance or the idea that all political voices deserve credence. I stress that Obama’s speech sought to widen public culture by building on rhetoric’s constitutive function to cultivate an attitude of tolerance. However, I argue that Obama’s rhetoric and attitude of tolerance fall short of shifting public policy and culture forward on the issues of same-sex marriage, gun control, and institutional racism. Tolerance in itself does not necessarily provide a solvent means to address contentious issues because it promotes the passive acceptance of plurality, rather than public transformation of a specific social harm and ill. As such, Obama’s rhetoric provides a seemingly optimistic vision for engaging public affairs by stressing the need for tolerance, but never fully advocates how a coalition of individual change agents can be mobilized into a community that has a central goal.
Keywords: Attitude; Barack Obama; Constitutive Rhetoric; Leadership; Presidential Rhetoric; Rhetorical Presidency